2021
DOI: 10.51470/plantarchives.2021.v21.s1.057
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Variation of Some Faba Bean Genotypes to Broomrape Infestation and Environmental Conditions

Abstract: Ten field experiments were carried out in Giza-Egypt during 2018/2019 and 2019/2020 seasons to elucidate the performance and extent of variation of some faba bean varieties to broomrape infestation under wide range of environmental conditions as sowing dates. During each season, five trials as sowing dates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Delaying faba bean sowing during Dec exhibited marked positive influences on all traits of 2018/019 season, whereas such date recorded slight positive influence only on seed yield per plot of 1 st season. Similar findings of faba bean genotypes to different sowing dates were reported in Egypt by (Al-Kaddoussi, 1996, Darwish, 1996, Abou-Taleb, 2006and Quarshie et al, 2021. Rank correlation coefficients among the environmental indices of the eight sowing dates for studied traits as well as accumulated GDD of 1 st (I), 2 nd (II) and 3 rd (III) growth periods across all planting dates are used to elucidate the nature of environmental effects and GDD (Table 5).…”
Section: Mean Effects Of Environmentssupporting
confidence: 55%
See 3 more Smart Citations
“…Delaying faba bean sowing during Dec exhibited marked positive influences on all traits of 2018/019 season, whereas such date recorded slight positive influence only on seed yield per plot of 1 st season. Similar findings of faba bean genotypes to different sowing dates were reported in Egypt by (Al-Kaddoussi, 1996, Darwish, 1996, Abou-Taleb, 2006and Quarshie et al, 2021. Rank correlation coefficients among the environmental indices of the eight sowing dates for studied traits as well as accumulated GDD of 1 st (I), 2 nd (II) and 3 rd (III) growth periods across all planting dates are used to elucidate the nature of environmental effects and GDD (Table 5).…”
Section: Mean Effects Of Environmentssupporting
confidence: 55%
“…The duration and dry matter accumulation of faba bean plants before flowering greatly depended on temperature and thermal units and soil moisture (Darwish et al, 2016) in addition to photoperiod (Confalone, et al, 2011). However, (Bishop et al, 2016 andQuarshie et al, 2021) concluded the importance of thermal units in the growth, development and seed yield of faba bean genotypes.…”
Section: Mean Effects Of Environmentsmentioning
confidence: 99%
See 2 more Smart Citations